PRIME-nurse practitioner competency model validation and criterion based OSCE rubric interrater reliability - Rita D’Aoust; Sarah E. Slone; Nancy Russell; Chakra Budhathoki; Catherine Ling (BMC Medical Education, 2024)
Abstract The PRIME-NP (Professional-Reporter-Interpreter-Manager-Educator/Evaluation-Nurse Practitioner) Model is adapted from the RIME (Reporter-Interpreter-Manager-Educator) model used in medical education to guide medical student and resident education. The Delphi technique was used to validate the PRIME-NP Model. After two rounds of review by a group of experts in NP curriculum, the model was determined to be valid based on expert consensus. Agreement percent increase from the first round to the second round in all categories. Interrater reliability (IRR) was assessed using interclass correlation after instrument validation was completed for each of the five levels of the PRIME-NP model. Overall, the IRR of the instrument was found to be acceptable with some notable exceptions. No variance was noted in professional behaviors at any level. Variance was increased in management and educator/evaluator behaviors in higher/later course levels. The PRIME-NP Model and PRIME-NP OSCE Rubric is a valid and reliable instrument to assess NP student progression in objective structured clinical examinations. This instrument has the potential for adaptation for use in other types of health sciences education and settings.